2002
DOI: 10.1007/978-3-662-07299-8
|View full text |Cite
|
Sign up to set email alerts
|

Forschungsmethoden und Evaluation

Abstract: Dieses Werk ist urheberrechtlich geschützt. Die dadurch begründeten Rechte, insbesondere die der Übersetzung, des Nachdrucks, des Vortrags, der Entnahme von Abbildungen und Tabellen, der Funksendung, der Mikroverfilmung oder der Vervielfältigung auf anderen Wegen und der Speicherung in Datenverarbeitungsanlagen, bleiben, auch bei nur auszugsweiser Verwertung, vorbehalten. Eine Vervielfältigung dieses Werkes oder von Teilen dieses Werkes ist auch im Einzelfall nur in den Grenzen der gesetzlichen Bestimmungen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
0
41

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(157 citation statements)
references
References 0 publications
1
115
0
41
Order By: Relevance
“…PBC items were aggregated to a mean index, with Cronbach's α = .53. While this does not meet common standards of α > .70, short scales consisting of few items are generally impaired by weaker measurement reliability (Bortz & Döring, 2006). According to the response scale, higher rankings indicate a lower level of PBC.…”
Section: Contextual Factorsmentioning
confidence: 85%
“…PBC items were aggregated to a mean index, with Cronbach's α = .53. While this does not meet common standards of α > .70, short scales consisting of few items are generally impaired by weaker measurement reliability (Bortz & Döring, 2006). According to the response scale, higher rankings indicate a lower level of PBC.…”
Section: Contextual Factorsmentioning
confidence: 85%
“…In terms of effect sizes, this would be considered large (i.e. an effect size of 0.51, where the effect size f 2 = R 2 /1 -R 2 , and f 2 values of 0.02, 0.15, and 0.35 are considered to indicate small, medium, and large effects, respectively [3]). Even when considering only the medical (5.4%) and psychosocial predictor sets (19.4%, see Table 4), these together explained 24.8% of the variation in the index, which in terms of an effect size (0.33) is also large and comparable with the findings of high quality prospective studies reported in the recent literature (see review in [15]).…”
Section: Discussionmentioning
confidence: 99%
“…[20] According to DIN 1319 [21] a measure is a predefined value. However, Bortz and Döring specify measurement as assigning values to an object, which not necessarily have to be physically predefined [22]. Based on this definition sensory studies are a form of measurement where descriptors are quantified.…”
Section: Targets Surface Measurements and Defines Distinctive Values mentioning
confidence: 99%